The Use of Virtual Learning Environments and Learning Management Systems During the Covid-19 Pandemic - McBurnie, Chris (EdTech Hub, 2020)
This technical note aims to inform the use and development of virtual learning environments (VLE) in educational responses to the current health crisis. It considers the advantages and disadvantages of a number of existing VLEs and includes guidance on selecting an appropriate VLE.
Keywords: COV:COVID and reopening of schools; COVID-19; Distance learning; EdTech; F: Helpdesk response; H: Distance education; LP: English; Learning management system; Remote learning; Virtual learning environment; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH